On the Biocompatibility of Fe3O4 Ferromagnetic Nanoparticles with Human Blood Cells - Stamopoulos, D.; Manios, E.; Gogola, V.; Niarchos, D.; Pissas, M. (JOURNAL OF NANOSCIENCE AND NANOTECHNOLOGY, 2010)
Magnetic particles are currently applied to special biomedical and environmental applications owing to their unique magnetic, morphological and substance-carrying capabilities. Very recently we introduced Magnetically Assisted Hemodialysis (MAHD), an innovative therapeutic application of Ferromagnetic Nanoparticles (FNs) for the treatment of End-Stage Renal Disease (ESRD). MAHD can be employed for the selective and efficient removal of toxins that, although of high biological importance, they cannot be handled by current Hemodialysis strategies. This work is focused on evaluating the biocompatibility of Fe3O4 FNs with cells of donated human blood, namely Red Blood Cells (RBCs), White Blood Cells (WBCs) and Platelets (Pits). To that end, optical microscopy and atomic force microscopy were employed for the morphological examination of blood cells that were maturated under the presence of Fe3O4 FNs by means of mild incubation up to 120 min at T = 20 degrees C. As a conclusion we have not detected noticeable interference between RBCs, WBCs and Pits with FNs for the maturation conditions and the extreme FNs concentrations examined in this work.